Switch to raltegravir decreases soluble CD14 in virologically suppressed overweight women: the Women, Integrase and Fat Accumulation Trial1. Issue 7 (10th February 2014) - Lake, JE; McComsey, GA; Hulgan, T; Wanke, CA; Mangili, A; Walmsley, SL; Stramotas, SA; Tracy, R; Currier, JS
<x xml:space="preserve">Abstract</x> Objectives Soluble CD14 (sCD14) is a monocyte activation marker associated with increased mortality in HIV infection. We assessed 48‐week changes in sCD14 and other inflammatory biomarkers in virologically suppressed, HIV‐infected women switching to raltegravir (RAL) from a protease inhibitor (PI) or nonnucleoside reverse transcriptase inhibitor (NNRTI). Methods HIV‐infected women with central adiposity and HIV‐1 RNA < 50 HIV‐1 RNA copies/mL continued their thymidine‐sparing nucleoside reverse transcriptase inhibitor (NRTI) backbone and were randomized to switch to open‐label RAL at week 0 (immediate) or 24 (delayed). In an exploratory analysis, inflammatory biomarkers were measured on stored fasting plasma. Results Of the 37 evaluable subjects, 78% were non‐White; the median age was 43 years, the median body mass index (BMI) was 32 kg/m2 and the median CD4 count was 558 cells/μL. At baseline, biomarker values were similar between groups. After 24 weeks, median sCD14 significantly declined in subjects switching to RAL [−21% (P < 0.001) vs. PI/NNRTI −5% (P = 0.49); between‐group P < 0.01]. After 48 weeks, immediate‐switch subjects maintained this decline and delayed‐switch subjects experienced a similar decline following the switch to RAL (−10%; within‐group P < 0.01). Immediate‐switch subjects also experienced an initial increase in tumour necrosis factor (TNF)‐α that was neither maintained after 48 weeks nor seen in delayed‐switch subjects. After adjustment for multiple testing, only declines in sCD14 remained significant. Conclusions In this randomized trial of women with central adiposity, a switch to RAL from a PI or NNRTI was associated with a statistically significant decline in sCD14. Further studies are needed to determine whether integrase inhibitors have improved monocyte activation profiles compared with PIs and/or NNRTIs, and whether measured differences between antiretroviral agents translate to demonstrable clinical benefit.